Comparison of the Effectiveness of Relapse Prevention Therapy Based on Neurofeedback and Cognitive Rehabilitation on Clinical Symptoms in Women Using Methamphetamine - Zeifodini, Bahareh; Mohammadi Shirmahale, Fatemeh; Tari moradi, Arezo; Belyad, Mohammadreza (Psychology of Woman Journal, 2025)
Objective: This study aimed to compare the effectiveness of neurofeedback-based relapse prevention and cognitive rehabilitation on pain perception and momentary craving in women with a history of methamphetamine use.Methods and Materials: The study employed a quasi-experimental design with a pre-test, post-test, and follow-up assessment. Participants included 86 women aged 20 to 40 years with a history of methamphetamine addiction who had undergone treatment and participated in recovery support programs. They were randomly assigned to the neurofeedback group (n = 43) or the cognitive rehabilitation group (n = 43). The interventions were conducted over five weeks, with neurofeedback training focusing on sensorimotor rhythm (SMR) and alpha-theta protocols, while cognitive rehabilitation targeted executive functions such as working memory, attention, and response inhibition. The McGill Pain Questionnaire (MPQ) and the Desire for Drug Questionnaire (DDQ) were administered at baseline, post-intervention, and follow-up. Data analysis was conducted using analysis of covariance (ANCOVA) and multivariate analysis of covariance (MANCOVA).Findings: The cognitive rehabilitation intervention significantly reduced total pain scores (F = 4.57, p = 0.039, η² = 0.100) and affective perception of pain (F = 4.94, p = 0.032, η² = 0.115), whereas the neurofeedback intervention did not show significant effects on pain (p > 0.05). Both interventions significantly reduced total momentary craving (Neurofeedback: F = 98.68, p < 0.001, η² = 0.701; Cognitive Rehabilitation: F = 64.64, p < 0.001, η² = 0.612) and its components, including desire and intention to use, negative reinforcement, and perceived control over substance use (p < 0.05). There was no significant difference in treatment effects between the two interventions (p > 0.05).Conclusion: Cognitive rehabilitation was effective in reducing pain, particularly affective pain perception, while both neurofeedback and cognitive rehabilitation significantly reduced momentary craving. These findings suggest that cognitive rehabilitation may be a more suitable intervention for pain management, while both interventions can be effective for craving reduction in individuals recovering from methamphetamine addiction.